Comparative Study Between Fuzzy and Sliding Mode Control Based on a BDFIG - Laid Ouada; B. Sebti (International Journal of Energetica)
Brushless doubly fed induction (BDFIG) is one of the best solutions of the previous research efforts about wind-power converter, which is represented by the absence of a brush gear and less maintenance cost, especially in the harsh regions. This task presents a comparative evaluation between a sliding mode and Fuzzy control. It demonstrates also the robustness of these two regulators against supply voltage and load disturbances. Furthermore, we have shown the undesirable phenomenon of oscillations having a finite frequency and amplitude, which is known as ‘chattering’ resulted from a sliding mode control which is based on Lyapunov approach theorem. The control of the system and BDFIG are both integrated in variable speed wind energy conversion. The performances of these control systems have been tested and analyzed in Matlab Simulink.